Radiological markers of idiopathic normal pressure hydrocephalus: Relative comparison of their diagnostic performance - Ryska, Pavel; Slezak, Ondrej; Eklund, Anders; Malm, Jan; Salzer, Jonatan; Zizka, Jan (Journal of the neurological sciences, 2020)
PURPOSE: Numerous radiological measures have been proposed as imaging biomarkers of idiopathic normal pressure hydrocephalus (iNPH), however, the number of studies systematically comparing their diagnostic values remains limited. The study objective was to compare the diagnostic performance of fifteen cross-sectional imaging iNPH biomarkers. MATERIALS AND METHODS: Eighty subjects were prospectively enrolled in the study: 35 subjects with clinically confirmed iNPH and 45 matched healthy controls (HC). Values of linear, angular and index measurements including three newly proposed biomarkers were obtained from 3T brain MRI studies by two independent readers. Diagnostic performance of biomarkers was studied by using receiver operating characteristic (ROC) analysis and t-statistic. RESULTS: All biomarkers studied were able to reliably differentiate iNPH subjects from HC (p < .001) except for cella media-to-temporal horn ratio. Z-Evans index, vertical cella media and vertical frontal horn diameters showed the highest discriminatory power between iNPH and HC groups (area under curve >0.99). Simple linear measurements of vertical (0.99) or horizontal (0.95) frontal horn diameters showed results comparable to calculated ratios, i.e. z-Evans (0.99) and Evans (0.96) indexes, respectively. CONCLUSION: The best diagnostic performance among fifteen radiological iNPH biomarkers was found in linear measurements referring to caudocranial alterations of the ventricular geometry, outweighing those referring to laterolateral ventricular enlargement (as e.g. commonly used Evans index). Simple linear measurements of vertical or horizontal frontal horn diameters showed comparable results to calculated, more time-consuming z-Evans or Evans indexes, respectively.
Keywords: Magnetic Resonance Imaging; normotenzní hydrocefalus; Hydrocephalus, Normal Pressure; lidé; senioři nad 80 let; senioři; mužské pohlaví; prospektivní studie; Cross-Sectional Studies; Female; Male; magnetická rezonanční tomografie; Aged; Prospective Studies; Aged, 80 and over; ženské pohlaví; průřezové studie; Humans